(untitled) (Research, Society and Development, 2019)
The urbanization process entails hydrological and environmental impacts on the water courses, highlighting the progressive loss of the potentials of its use, with consequences on the quantity and quality of water. In this sense, this article aimed at the hydrological and morphometric characterization of the hydrographic basin formed by the drainage channels of avenues Carlos Drummond de Andrade, Carlos de Paula Andrade, Cristina Gazire and Mayor Li Guerra, located in the central region of Itabira (MG). For this, the documentary research was used to analyze the use and occupation of the soil and field surveys were carried out to identify the geometry and maximum flow of the channels. Regarding the morphometric analysis, the roughness coefficient and the compactness index indicate that the analyzed basin is flood prone. It was verified that the geometry of the channels varies from trapezoidal to mixed section (lateral with rectangular geometry and triangular bed). Considering the hydrological analysis, it was noticed that the maximum flow of the channel of Avenue Mayor Li Guerra, located in the downstream portion of the basin, does not support the project flow obtained by the rational method for a 50-year return time. Thus, to reduce the negative impacts related to floods, it is suggested to compensate for the maintenance of green areas, regulation of soil use, infiltration wells, infiltration ditches and the use of permeable pavements.